Power sector reform-blackouts before policy. - Baker, G.
Over the last decade, in developing countries everywhere from Asia to the Americas, government-run utilities have been on notice that their financing must change. The private sector must somehow replace the World Bank as the main source of funding for energy projects in general and for electric-power facilities in particular. The recent history of many of those nations has been discouraging. Warnings from the World Bank proved inadequate. Ultimately only an ugly and embarrassing series of outages in major metropolitan areas prompted effective action to privatize power and energy-a "reform-by-blackouts," if you will. Mexico is the gateway between North and South America, a rising industrial power, and a key trading partner of the United States. It serves as an assembly and manufacturing site for the subsidiaries of international companies, which export their products mainly to the US market. Industrial exports account for more than 20 percent of total industrial power demand. And once again, it remains to be seen whether policymakers in the government and their opponents in the Mexican Congress can jointly bring structural reforms to an inefficient state-run monopoly before a string of costly and dangerous blackouts forces drastic action. The outcome will affect not only Mexico and its North American trading partners, but will be of keen interest to a number of other large developing countries. India, for one, is also grappling with an aging electrical infrastructure, high government subsidies for electricity, predictions of steep increases in demand, and stubborn legislative resistance to privatization plans
Keywords: India; Mexican Congress; Mexico; Blackouts; Developing countries; Electric-power facilities; Energy projects funding; Government-run utilities; Inefficient state-run monopoly; Major metropolitan area power outages; Policy; Power sector reform; Private sector; Privatization; Structural reforms